Puerperal home visit as a strategy for nursing care in primary health care: integrative review - Bernardi, Mariely Carmelina; Carraro, Telma Elisa; Sebold, Luciara Fabiane (Rev Rene, 2011)
This work stands for an integrative review of literature developed to identify and discuss different contributions for practicing, the knowledge produced between January 2006 and December 2010, about nursing care of postpartum at home. The search for the articles was performed by means of the descriptors: the postpartum period and nursing care, in databases like: BDENF, SciELO, CINAHL, MEDLINE and LILACS. 10 articles were analyzed and they contemplate: practices used in breast problems, home as an educational and care space, postpartum experience, nursing diagnosis, care actions performed by the father, care involving the family, in addition to the beliefs and taboos. The results confirmed a discrete production of knowledge on the subject, which is relevant to the improvement of studies on home visits to postpartum women in the primary care.